Resultados Gestacionales asociados al tratamiento antipsicótico durante el embarazo: Una revisión narrativa.: Obstetric outcomes associated with antipsychotic treatment during pregnancy: A narrative review. - Sanchez Guanilo, Jessica Patricia (2022)
Antipsychotics are increasingly prescribed for various disorders including bipolar disorder, schizophrenia, other psychotic disorders and to a lesser extent for depression, anxiety, insomnia and even nausea during pregnancy. The full knowledge about its possible effects due to exposure during pregnancy is still limited, although some studies refer to some degree of relationship with the appearance of effects such as gestational diabetes, premature birth, congenital malformations, our review did not find a sufficiently clear relationship with them. In addition to the safety profile, another aspect to consider is the assessment that untreated psychiatric disorders could also represent a risk factor for poor pregnancy outcomes. Therefore, due to the lack of highly significant data on these aspects during pregnancy, more studies are needed to provide more detail on the risks and benefits of these drugs at this stage.